Cardiovascular‐interventional‐surgery virtual training platform and its preliminary evaluation. Issue 3 (13th October 2014) - Zhou, Chaozheng; Xie, Le; Shen, Xianglong; Luo, Maisheng; Wu, Zhaoli; Gu, Lixu
Abstract Background Cardiovascular interventional surgery (CIS) training has mainly been performed with fluoroscopic guidance on animals. However, this has potential drawbacks, including from the anatomical differences between animal models and the human body. The purpose of this research is to develop a virtual training platform for inexperienced trainees. Methods The CIS virtual training platform is composed of a mechanical manipulation unit, a simulation platform and a user interface. A decoupled haptic device offers high‐quality force feedback. An efficient physically based hybrid model was simulated. The CIS procedure was tested with three simulation studies. Results Translational and rotational tests were employed to preliminarily evaluate the platform. Tests showed that accuracies improved by 50% and 32.5%. Efficient collision detection and continuous collision response allowed real‐time interactions. Furthermore, three simulation studies indicated that the platform had reasonable accuracy and robustness. Conclusions The proposed simulation platform has the potential to be a good virtual training platform. Copyright © 2014 John Wiley & Sons, Ltd.